Perkembangan Gunung Agung, Kebencanaan, dan Persoalan Pengungsi - Dewa Made Indra (Bali Membangun Bali: Jurnal Bappeda Litbang, 2018)
Mount Agung in Karangasem Regency is one of the volcanoes in Bali. This mountain is in the path of the Pacific Ring of Fire. Towards the end of 2017 and the beginning of 2018, the mountain which is highly purified by the Balinese Hindu community are erupted. Although the eruptions were not as large as in 1963, thousands of people during 2017 were displaced not only around Karangasem Regency but also in some others in Bali. This qualitative study found that, until the eruption in 2017 and 2018, Mount Agung is said to be still in a state of disaster. For that reason, there are still residents who reside less than 4 kilometers from the peak of Mount Agung lived in refugee camps. Nevertheless, in general the problem of evacuation can be said to have been going well.